Our experience with single patch repair of complete atrioventricular septal defects - Vuran, Can; Turkoz, Riza; Yoruker, Uygar; Omay, Oguz; Saritas, Bulent; Ayabakan, Canan; Sarisoy, Ozlem; Turkoz, Riza (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Various surgical methods have been utilized in the management of complete atrioventricular septal defects (CAVSD). Early intervention and achievement of a competent left atrioventricular valve are the key factors for successful treatment. Methods: A total of 66 patients with complete atrioventricular septal defect have been operated in a tertiary care center. Patient group consisted of 28 males and 38 females with an average age of 6.2 ± 3.3 months. Ventricular and atrial defects were repaired generally with single-patch technique using autogenous pericardium. Results: Preoperative catheterization and angiography was performed in 41 patients. Single patch and modified single patch techniques were preferred in 57 and 9 patients respectively. The average duration for respiratory support, intensive care unit stay and discharge from hospital were 36 ± 49.3 hours, 4.1 ± 1.9 days, and 10.1 ± 3.3 days respectively. In the left atrioventricular valve mild, moderate and severe regurgitation were detected in 44 (66.6%), 17 (25.7%) and 2 (3%) patients postoperatively. No regurgitation was determined in 3 patients (4.5%). Two cases ended up with mortality (3%). Conclusion: Single patch repair technique can provide satisfactory surgical outcomes in patients with complete atrioventricular septal defect.